2014
DOI: 10.1103/physrevd.89.105024
|View full text |Cite
|
Sign up to set email alerts
|

Quantum entanglement in analogue Hawking radiation: When is the final state nonseparable?

Abstract: We study the quantum entanglement of the quasiparticle pairs emitted by analogue black holes. We use a phenomenological description of the spectra in dispersive media to study the domains in parameter space where the final state is non-separable. In stationary flows, three modes are involved in each sector of fixed frequency, and not two as in homogeneous situations. The third spectator mode acts as an environment for the pairs, and the strength of the coupling significantly reduces the quantum coherence. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 40 publications
3
97
0
Order By: Relevance
“…The Hawking spectrum |S ud2 | 2 shows a peaked structure, with a decaying envelope similar to that of non-resonant spectra, which are known to be approximated quite well in a wide range of frequencies by a Planck distribution [18,27,52,56] …”
Section: A Ideal Optical Latticementioning
confidence: 99%
See 2 more Smart Citations
“…The Hawking spectrum |S ud2 | 2 shows a peaked structure, with a decaying envelope similar to that of non-resonant spectra, which are known to be approximated quite well in a wide range of frequencies by a Planck distribution [18,27,52,56] …”
Section: A Ideal Optical Latticementioning
confidence: 99%
“…However, due to the non-perfect stationarity of the GP wave function, the corresponding relative quasi-particle current for the quasi-stationary BdG modes is also inhomogeneous, which implies that the corresponding S-matrix is not pseudo-unitary. Nevertheless, since the region near ω = 0 is not interesting for the observation of the spontaneous Hawking effect [16,18,53], for practical purposes we can restrict the computations to the range ω > ω Λ , ω Λ being a numerically enforced cut-off of order ω Λ ∼ 10 −2 µ 0 ≫ σ(t) so condition (19) is fulfilled and the stationary BdG approximation (20) is expected to be valid.…”
Section: Quasi-stationary Scattering Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear that we can infer robustness under dissipation from robustness under dispersion, since dissipation alters the past propagation of the outgoing modes even more drastically, and we might therefore expect that the deviations due to dissipation could differ considerably from those due to dispersion. Indeed, in a recent theoretical study of a modulated Dynamical Casimir Effect [23], it was found that a relatively small rate of dissipation can have a significant effect on the properties of the emitted radiation, in particular on the entanglement of the pairs produced, i.e., on the nonseparable character of their state, which is the property that allows us to distinguish the stimulated (classical) effect from the spontaneous effect due to vacuum fluctuations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The solution of the previous indefinite integral is given in terms of elliptic functions. The resulting phase of the wave function is computed from Equation (19), obtaining:…”
Section: Solutions Of the Homogeneous Gross-pitaevskii Equationmentioning
confidence: 99%